Crystal plasticity analysis of temperature-sensitive dwell fatigue in Ti-6Al-4V titanium alloy for an aero-engine fan disc. (March 2022) - Yin, Liangwei; Umezawa, Osamu
Highlights: Evolutions of activation energy and volume with temperature have a significant impact on the strain rate sensitivity of single crystal α -titanium. The temperature-dependent stress redistribution in Ti-6Al-4 V alloy is linked to the variation in the strain rate sensitivity and underlying mechanisms. The bore of the fan disc with high hoop stress and low stress triaxiality is the most detrimental site for dwell facet nucleation. The local stress redistribution at the bore of the Ti-6Al-4 V fan disc in service is dominated by the applied stress level and size of macrozones rather than the high strain rate sensitivity at working temperatures. Abstract: This study investigates the temperature-dependent dwell fatigue behavior of Ti-6Al-4V alloy using crystal plasticity finite element method. The dislocation mechanism-based crystal plasticity parameters are calibrated with the data of quasi-static tensile and constant load creep tests at ambient and intermediate temperatures. In particular, the rate-dependent parameters related to slip property are employed to establish the relationship between strain rate sensitivity of a soft α -titanium single crystal and temperature. The variation of strain rate sensitivity with temperature influences the stress redistribution occurring within the hard-soft grain combination, which in turn affects the dwell fatigue sensitivity. Further, the structural analysis for a Ti-6Al-4V fan disc provides the stress fields at takeoff and cruise phases to examine the in-service stress redistribution. The highly localized hoop stress and presence of large macrozones at the bore of the fan disc, rather than the fair rate sensitivity of soft macrozones at working temperatures, are responsible for triggering basal stress enhancement and dwell facet nucleation in hard macrozones.